Les verbes inchoatifs commencer, s’appreter, se mettrea et terminatifs finir, cesser de en combinaison avec l’infinitif dans la traduction slovene – possibilitée manquée pour l’exploration lexicale ? - Schlamberger Brezar, Mojca (Linguistica (Ljubljana), 2024)
Aspect is realized in different way in different languages and can be expressed by gram-matical as well as lexical means. Verbal inchoative and terminative paraphrases intro-duced with French ingressive verbs commencer, s’appreter a, se mettre a + infinitive, and egressive verbs cesser,finir + infinitive have an equivalent phasal form in Slovene, namely začeti + infinitif and nehati + infinitive. Slovene, a Slavic language can mark the phasal aspect with verbal prefixes.The paper compares ingressive verbal paraphrases commencer, se mettre a, s’appreter a and egressive verbs finir, cesser de, followed by an infinitive, with their translations into Slovene taken from the FraSloK bilingual corpus, which is a part of the Spook corpus. An analysis of the translations of these verbal paraphrases into Slo-vene shows that it is possible to find not only solutions that are structurally equivalent to ingressive verb začeti + infinitive or egressive verbs nehati + infinitive or končati + 81noun, but also those that are translated by means of verbal prefixes or adverbs. In the translations analysed, however, realizations with incohative or terminative periphrastic constructions prevail.
Keywords: aspect inchoatif; aspect terminatif; corpus traductionnel français – slovene; francosko-slovenski prevodni korpus; French-Slovene translation corpus; inchoative aspect; končni glagolski vid; opisna glagolska predpona; périphrase verbale; préverbe; terminative aspect; verbal paraphrase; verbal prefix; začetni glagolski vid